2022
DOI: 10.1002/hfm.20965
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of musculoskeletal discomforts among mining truck drivers with respect to human vibration and awkward body posture using random forest algorithm

Abstract: Using Random Forest algorithms, this study aimed to investigate musculoskeletal discomforts among mining truck drivers considering human vibration and awkward body posture. The study was conducted on 65 professional male drivers of mining trucks. The Cornell questionnaire was used to determine musculoskeletal discomforts.Drivers' exposure to vibrations was measured using the Svanteck 106 A vibration meter. The body posture was analyzed using the quick exposure check (QEC). The main mechanical and individual ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Similarly, a study from Nigeria reported that the majority of bus drivers experienced musculoskeletal discomfort, particularly in the lower back, knees, neck, upper back, and shoulders, with psychological factors and work pressure also cited as contributing causes [24]. Furthermore, studies on mining truck drivers and elderly Malaysian taxi drivers emphasize the role of age, awkward body posture, and body vibrations in musculoskeletal discomfort, highlighting the prevalence of back pain, especially among older drivers who often smoke and use budgeted vehicles [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study from Nigeria reported that the majority of bus drivers experienced musculoskeletal discomfort, particularly in the lower back, knees, neck, upper back, and shoulders, with psychological factors and work pressure also cited as contributing causes [24]. Furthermore, studies on mining truck drivers and elderly Malaysian taxi drivers emphasize the role of age, awkward body posture, and body vibrations in musculoskeletal discomfort, highlighting the prevalence of back pain, especially among older drivers who often smoke and use budgeted vehicles [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Buses, in particular, represent a dominant form of public transportation adopted by countless commuters. Throughout their regular duties, bus drivers encounter notable levels of vibrations and noise, which are recognized as occupational hazards [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The drivers of heavy vehicles (i.e. truck and bus) have the potential to be exposed to amounts of noise and vibration [ 11 , 12 ]. The bus drivers have an important role in public transport and are most useful for alleviating the traffic load as well as air pollution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%